HPLC-Method for the Quantification of Carvedilol in Human Plasma - Chatterjee, Bappaditya; Das, Ayan; K. Pal, Tapan (Asian Journal of Chemistry, 2010)
A simple and feasible reversed phase high performance liquid chromatographic (RP-HPLC) method coupled to UV detection for the determination and quantification of carvedilol in human plasma has been described. After sample preparation by one step liquid-liquid extraction with ethyl acetate, carvedilol and carbamazepine (internal standard) were chromatographically separated on a hypersil BDS, C18 (250 mm × 4.6 mm, 5 μm) column using a mobile phase composed of 10 mM potassium dihydrogen phosphate buffer (pH adjusted to 3.5) and acetonitrile in a ratio of 60:40 (v/v) at an isocratic flow rate of 1 mL/min. The wavelength of detection was set at 242 nm. Retention time of carvedilol and internal standard (carbamazepine) were 9.50 and 4.47 min, respectively. The assay was linear between the concentration ranges of 4-60 ng/mL for carvedilol in plasma with a satisfactory correlation coefficient (r2) value above 0.9965. The extraction recovery of carvedilol in plasma at three quality control samples was ranged from 83.943-91.672 %. The method was specific and sensitive with the limit of quantification of 4 ng/mL. The accuracy and precision values obtained from six different sets of quality control samples analyzed in separate occasions were within the satisfactory limit. In stability study, carvedilol in human plasma was stable during storage and assay procedure. The developed and validated method is simple, sensitive and economical and can be successfully applied to the pharmacokinetic study of carvedilol in human volunteers.